2004
DOI: 10.1136/bmj.329.7466.581
|View full text |Cite
|
Sign up to set email alerts
|

Using monoamine oxidase type B inhibitors in Parkinson's disease

Abstract: They are effective and safe, at least when used alone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Identification of MAO inhibitors is of great interest in drug discovery (Kalgutkar et al, 2001;Yan et al, 2004). MAO A inhibitors have been used as antidepressants (Nolen et al, 1993), and MAO B inhibitors in the treatment and prevention of Parkinson's disease (Ben-Shlomo and Bhatia, 2004). The oxidation of biogenic amines by MAO results in the production of hydrogen peroxide and aldehydes which may represent a risk factor for cell oxidative injury (Cohen et al, 1997;Hauptmann et al, 1996;Vindis et al, 2000;Youdim and Lavie, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of MAO inhibitors is of great interest in drug discovery (Kalgutkar et al, 2001;Yan et al, 2004). MAO A inhibitors have been used as antidepressants (Nolen et al, 1993), and MAO B inhibitors in the treatment and prevention of Parkinson's disease (Ben-Shlomo and Bhatia, 2004). The oxidation of biogenic amines by MAO results in the production of hydrogen peroxide and aldehydes which may represent a risk factor for cell oxidative injury (Cohen et al, 1997;Hauptmann et al, 1996;Vindis et al, 2000;Youdim and Lavie, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There was concern, for example, about the utility of transplantation and second transplantations [ 32 , 53 ]. In a similar vein, there was discussion about whether risk factors such as alcoholism should be taken into account in access to transplantation [ 54 , 55 ]. Also widely discussed was how gender, ethnic, geographic and socio-economic differences affect access to transplantation [ 37 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, PP increases with age and is strongly related to the early development of large vessel atherosclerosis (8,9). Increased carotid intima-media thickness (IMT) and carotid and/or iliofemoral plaque are frequent in hypertensive subjects, but their relationship with PP has been rarely studied (10). However, some studies, both cross-sectional and prospective (8)(9)(10)(11)(12)(13)(14)(15), have found an association between PP and carotid IMT and its progression, respectively, as summarised in Table 1.…”
Section: Graham Jacksonmentioning
confidence: 99%
“…Concern has been raised regarding the use of MAO‐B inhibitors and an increase in mortality. A meta‐analysis of the use of these drugs in early disease, however, allayed these concerns (9), but the recommendation seems to be that these drugs are safe for use as a monotherapy in young and generally well PD patients (10). In practice, the majority of the PD patients are older and get frail as the disease advances.…”
mentioning
confidence: 99%